Max Weber as an Economist: Revisiting Max Weber's Legacy 100 Years after His Passing - Marek Louzek (Journal of Contextual Economics – Schmollers Jahrbuch, 2020)
This article presents Max Weber as an economist and as a social scientist. Weber's relations to economics, philosophy and sociology are discussed. Max Weber has more in common with economists than it might seem at first sight. His principle of value neutrality has become the foundation of the methodology of social sciences, including economics. The second point shared by Max Weber with standard economics is methodological individualism. The third point which a modern economist can learn from Max Weber is the concept of the ideal type.
Keywords: B15; A14; A15; 330; Institutional Economics; Economic Sociology; Protestant Ethic; Methodology of Economics